Alternative Histories: Philip Roth and The Plot Against America (American & British Studies Annual, 2010)
This paper deals with Philip Roth’s continual idea of “what if…” with a concentration on his novel, The Plot Against America. Roth has always called himself a suppositional writer, though Roth, (who is Roth?) is a continual presence in his work (Zuckerman and Kepesh, for example, in other writerly personae). Nevertheless, this work makes us question various ideas about twentieth-century American history, not only in terms of the personal, but also in terms of ideas about nationality. This is a novel that is both comic and tragic and which makes us think about our position in the contemporary world of Central and East Europe. More importantly, it makes us think about what is happening in contemporary America. It also questions ideas about Roth as author.
Keywords: American identity; American nationalism; Jewishness; anti-Semitism; dystopia; Philip Roth; The Plot Against America